1974
DOI: 10.1128/jb.120.2.569-578.1974
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Copy Mutant of the Bacteriocinogenic Plasmid Clo DF13

Abstract: After nitrosoguanidine mutagenesis, strain Escherichia coli P678-54, bacteriocinogenic for Clo DF13, yielded a mutant strain that showed an enhanced bacteriocin production. The results from conjugation experiments indicated that the mutation, responsible for the enhanced bacteriocin production, is located on the Clo DF13 plasmid. The following properties of strains harboring the mutant Clo DF13 plasmid could be observed. (i) The bacteriocin production in these strains can be further enhanced at least fourfold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…The E. coli strain used in this study, the minicell-producing strain P678-54 (1), has the following markers: thr, ara, leu, azi, tonA, lacY, minA, gal, minB, rpsL, malA, xyl, mtl, thi, supE. The CloDF13 cop-3 replication control mutant has been described previously (13,37). All transposon mutants used in this study and listed in Table 1 (35).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The E. coli strain used in this study, the minicell-producing strain P678-54 (1), has the following markers: thr, ara, leu, azi, tonA, lacY, minA, gal, minB, rpsL, malA, xyl, mtl, thi, supE. The CloDF13 cop-3 replication control mutant has been described previously (13,37). All transposon mutants used in this study and listed in Table 1 (35).…”
Section: Methodsmentioning
confidence: 99%
“…The small nonconjugative plasmid CloDF13, is present in Escherichia coli to an extent of about 10 copies per cell (36). Copy control mutants of CloDF13 have been isolated (3, 13), such as CloDF13 cop-3 with a plasmid copy number of about 70 (37). As revealed from experiments with E. coli minicells, CloDF13 encodes for the synthesis of at least eight proteins (4).…”
mentioning
confidence: 99%
“…Previous studies have shown that the bacteriocinogenic plasmid CloDF13 replicates unindirectionally from a unique origin, which is located at 2.8% on the CloDF13 physical map (1). In our study on the control of CloDF13 replication, we used both conditional (2,3) and nonconditional (4) plasmid copy number (cop) mutants. It was shown that the region between 1.8% and 11.5% of the plasmid genome contains sufficient information for autonomous plasmid DNA replication.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmid Clo DF13, with a molecular weight of 5.75 MegaDaltons (MD), has been extensively used in our laboratory to study the replication, gene function and genetic organisation of bacterial plasmids (1)(2)(3)(4)(5)(6)(7). It was observed that this plasmid, which is present in Escherichia coli to the extend of about 10 copies per cell, directs the synthesis of at least four m-RNA's and eight proteins (2,6).…”
Section: Introductionmentioning
confidence: 99%
“…2.8 MD) mediates ampicillin resistance and is derived from the R plasmid pRI 30 (13). To study the expression of plasmids we employed both in vivo and in vitro systems developed previously (1,6,15). Analysis of Clo DF13::Tn901 insertion mutants in these systems revealed that insertion of transposon Tn901 within Clo DF13 might result in the disappearance or alteration of particular plasmid specified polypeptides (16).…”
Section: Introductionmentioning
confidence: 99%